The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/universe8020060
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum Energy in Saez-Ballester Theory and Stabilization of Extra Dimensions

Abstract: In this work, we study a spherically symmetric metric in 5D within the framework of Saez-Ballester Theory, where minimal dark energy-matter interaction occurs. We predict that the expanding isotropic universe will be progressively DE dominated. We estimate few values of the deceleration parameter, very close to the recently predicted values. We obtain the value of the DE EoS parameter as ω=−1. Additionally, we measure the value of the overall density parameter as Ω=0.97(≈1), in line with the notion of a close … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 147 publications
0
2
0
Order By: Relevance
“…Kiran et al [12] discussed spatially homogeneous and anisotropic Bianchi type-III bulk viscous fluid string cosmological model in gravity. Singh et al [13] considered a five-dimensional spherically symmetric space-time within the framework of Saez-Ballester theory, wherever minimal dark energy-matter interaction occurs. Bhabor et al [14] studied fivedimensional Bianchi type-I string cosmological models with bulk viscous fluid in Lyra geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Kiran et al [12] discussed spatially homogeneous and anisotropic Bianchi type-III bulk viscous fluid string cosmological model in gravity. Singh et al [13] considered a five-dimensional spherically symmetric space-time within the framework of Saez-Ballester theory, wherever minimal dark energy-matter interaction occurs. Bhabor et al [14] studied fivedimensional Bianchi type-I string cosmological models with bulk viscous fluid in Lyra geometry.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the latter, the SB theory includes the action of ordinary matter that is not coupled to the SB scalar field. Various cosmological models have been established in the context of the SB theory to study open problems in both the classical and quantum regimes [49][50][51][52][53][54]. Applying the similar reduction procedure used to construct the MBDT, without assuming the presence of the higher dimensional matter fields and imposing the cylindricity condition on the extra coordinate, it has been shown that the SB field equations associated to the bulk split into four sets of effective field equations on any hypersurface orthogonal to the extra dimension [9].…”
Section: Introductionmentioning
confidence: 99%